English for a Successful Career: Studying the Needs of the Students Majoring in Economics and Socio-Political Studies - Stefanova, Albena (Research Papers, 2022)
The academic courses in English for specific purposes (ESP) are aimed at honing student functional communicative competence. This will contribute to students’ full development as highly qualified experts in the particular professional area as well as to their successful career realisation. To achieve this goal it is necessary to ensure optimal effectiveness of the ESP courses which involves studying student needs, taking into account the specific features of the new generations of learners – ways of perception, communication and learning, and employing modern information and communication technologies and teaching methods. In addition, the results from surveys of student and employee needs carried out worldwide should also be borne in mind.
Keywords: English for specific purposes; English for students of economics; Needs analysis; English for students of socio-political studies